Comparison of spinal anesthesia with combined sciatic-femoral nerve block for outpatient knee arthroscopy (2008)
Study Objective: To compare spinal anesthesia and combined sciatic-femoral nerve block for outpatient knee arthroscopy. Design: Prospective, randomized, controlled study. Setting: Postoperative recovery area at a university-affiliated medical center. Patients: 50 ASA physical status I and II adult outpatients undergoing arthroscopic knee surgery. Interventions: Study subjects were equally divided (n = 25 each) into spinal and sciatic-femoral groups. Spinal group patients received spinal anesthesia with 7.5 mg of 0.5% hyperbaric bupivacaine. Sciatic-femoral group patients received combined sciatic-femoral nerve blocks using a mixture of 20 mL of lidocaine 2% plus 20 mL of bupivacaine 0.5%. Measurements: Times including that from arrival in the operating room to readiness for surgery, duration of surgery, recovery time, and patient satisfaction were recorded. Analgesia and occurrence of adverse events also were recorded. Main Results: No significant differences between the two groups were found for any of the study measurements of recovery. After discharge, postoperative pain differed significantly between groups only at 6 hours (P less than 0.002). Patient satisfaction was high with both techniques. Conclusions: Combined sciatic-femoral nerve block for outpatient arthroscopic knee surgery offers satisfactory anesthesia, with a clinical profile similar to that of low-dose spinal anesthesia. Sciatic-femoral nerve blocks are associated with significantly lower pain scores during the first 6 postoperative hours. © 2008 Elsevier Inc. All rights reserved.